A convex combination method for quantile regression with interval data - Somsak Chanaim (2018)
© 2018, Springer International Publishing AG. This paper studies a quantile regression under asymmetric Laplace distribution (semi-parametric model) with interval valued data. Generally, the center point of the interval data has been used to represent the sample data for estimated parameter of the model. This paper uses the convex combination method to find the best point to estimate parameter in the quantile regression model. We apply the quantile capital asset pricing model (quantile CAPM) to present the result.